Synthesis and characterization of graphene and carbon nanotubes for removal of heavy metals from water - Thema, Force Tefo (Vaal University of Technology, 2012)
The commercial flake graphite was prepared into functionalized graphite oxide (GO) by adopted chemical treatment. After the exfoliation and intercalation of graphite into functionalized graphene oxide that formed stable colloidal dispersion in polar aprotic solvent, the reduction process was undertaken by continuous stirring with hydrazine hydrate in a microwave at 35 oC for two hours. The reduced material was characterized by X-ray diffraction (XRD), attenuated total reflectance (ATR) FT-IR, Ultra-violet visible (UV-vis), atomic force microscopy (AFM), transmission electron microscopy (TEM), scanning electron microscopy (SEM), Raman microscopy and magnified optical microscopy that confirm the oxidation of graphite and reduction of graphene oxide into graphene sheets. Carbon nanomaterials were synthesized from Co-Sn, Co-Sr and Co-Zn as catalysts supported on Al2O3, CaCO3 and MgO. The as-prepared nanomaterials were characterized by thermogravimetric and derivative thermogravimetric analysis (TGA & DTA), Raman spectroscopy, scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) and the transmission electron microscopy. The intensity ratios (ID/IG) of the D- and G- bands were found to be the same that is averagely at 0.83. The TGA & DTA curves have shown Co-Sn/Al had significant weight loss, Co-Sr/Mg weight loss and decomposition, Co-Sr/Al decomposition and Co-Zn/Mg weight loss. However these weight losses were not significant. The EDS analysis showed all elements which took part in the reaction confirming the success of each synthesis. The SEM images show carbon nanotubes only on samples that have been synthesized on MgO as confirmed by TEM images. Finally the XRD showed some characteristic peaks at desired peaks except that they were other peaks attributed to impurities and armophous carbon. It was also observed that Co-Sn/Ca and Co-Sn/Mg XRD curves showed broad peaks at theta = 24.3o & 42.6o and theta = 23.9o & 43.1o respectively which are lattice structure characteristic peaks.
M-Tech. (Department of Chemistry, Faculty of Applied and Computer Science), Vaal University of Technology.
Keywords: synthesis, characterization, graphene, carbon nanotubes, removal of heavy metals, water.; Dissertations, Academic -- South Africa; Carbon nanotubes; Graphene; Heavy metals; Green technology